The Roles of Social Value Orientation and Anticipated Emotions in Intergroup Resource Allocation Decisions - Bono, Suzanna Awang; van der Schalk, Job; Manstead, Antony S. R. (Frontiers in Psychology, 2020)
How individuals divide resources between themselves and another person is influenced both by their social value orientation (SVO) and the emotions they expect to feel when dividing resources (anticipated emotions). Research has also shown that individuals favor members of their own group (ingroup) over individuals from other groups (outgroup) when allocating resources. The Malaysian multi-ethnic population is a highly relevant context to study the effects of intergroup relations on anticipated emotions and resource allocation. The current studies recruited Malaysian participants to examine whether anticipated emotions and allocation behavior are influenced by the ethnic identity of the person receiving the allocation. Participants completed an SVO measure and rated how they would feel if they were to share resources equally or unequally. They then made allocations between themselves and an ingroup or outgroup member in an economic game. There was no evidence of ingroup favoritism in anticipated emotions and allocation behavior. This may have been due to impression management, social desirability concerns, and/or the use of a population with socially liberal attitudes. The results nevertheless provide support for the notion that anticipated emotions play a key role in resource allocation decisions.